Selectorate theory and the democratic peacekeeping hypothesis: evidence from Fiji and Bangladesh. Issue 1 (1st January 2016) - Levin, Jamie; MacKay, Joseph; Nasirzadeh, Abouzar
ABSTRACT: UN peacekeeping has undergone two major shifts since the end of the cold war. The first is a move away from limited efforts to maintain peace in post-conflict environments towards more robust efforts at peace enforcement. Second, the composition of peacekeepers has changed. In 1990, the leading contributors of personnel to UN peacekeeping missions were notable supporters of multilateral cooperation and other liberal-democratic norms with extensive peacekeeping experience. As of 2012, however, the top contributors to UN peacekeeping missions had changed dramatically: Bangladesh, Pakistan, Ethiopia and Nigeria have replaced traditional peacekeepers Canada, Finland, Austria and Norway. While liberal-democratic nations continue to bear most of the costs, they have all but disappeared on the ground, leading to a precipitous decline in the quality of peacekeeping. The consequences of the latter shift are the subject of considerable debate. Some argue that peacekeeping facilitates the transmission of democratic norms and institutions to sending states. Others increasingly argue that the so-called 'democratic peacekeeping' hypothesis is a 'myth'. We go further, suggesting that autocratic states may take on peacekeeping duties as a way of maintaining costly security apparatuses for the purposes of domestic repression. Peacekeeping – a feature of liberal post-cold war global governance – risks becoming a means to facilitate illiberal domestic governance in the developing world. We demonstrate this in two tentative but cautionary cases: Fiji and Bangladesh.